2017
DOI: 10.1364/oe.25.023051
|View full text |Cite
|
Sign up to set email alerts
|

Optical chirality breaking in a bilayered chiral metamaterial

Abstract: We propose a planar optical bilayered chiral metamaterial, which consists of periodic metallic arrays of two L-shaped structures and a nanorod twisted on both sides of a dielectric slab, to investigate the optical chirality breaking effect by using finite-difference time-domain (FDTD) method. Even the metamaterial is with chiral symmetry, an optical chirality breaking window in the asymmetric transmission pass band is obtained in chiral metamaterial structure. We analyze the plasmonic mode properties and attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Many new properties have been found in the chiral metamaterials, such as asymmetric transmission (AT), circular dichroism and optical activity. Asymmetric transmission, dened as the difference between the transmittance in two opposite propagation directions, has been largely reported on planar metasurfaces in microwave, [5][6][7][8][9][10][11][12] THz, 13-20 infrared 21 and optical [22][23][24][25][26][27][28] regimes. It was found that a chiral metamaterial with symmetry breaking can exhibit an AT effect for linear and circular polarizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many new properties have been found in the chiral metamaterials, such as asymmetric transmission (AT), circular dichroism and optical activity. Asymmetric transmission, dened as the difference between the transmittance in two opposite propagation directions, has been largely reported on planar metasurfaces in microwave, [5][6][7][8][9][10][11][12] THz, 13-20 infrared 21 and optical [22][23][24][25][26][27][28] regimes. It was found that a chiral metamaterial with symmetry breaking can exhibit an AT effect for linear and circular polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a chiral metamaterial with symmetry breaking can exhibit an AT effect for linear and circular polarizations. 10,[27][28][29][30][31][32] For the experimental observations of AT, several metamaterials with AT effects are reported. In the microwave band, Mutlu et al 7 demonstrated a narrow asymmetric transmission of linear polarization at 7.1 GHz with T yx ¼ 0.171 and T xy ¼ 0.974.…”
Section: Introductionmentioning
confidence: 99%
“…In EIT-like or EIR-like effect, dark mode is designed to couple with bright mode, leading a destructive interference between the bright mode and dark mode. The EIT-like effect has also been introduced to a chiral metamaterial [22] to break the asymmetric transmission in a narrow pass band, which provides a new way in manipulation light propagation. However, the resonant antenna is made of metal and cannot be dynamically controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigate the polarization conversion effect for different Fermi energies of BDS rod, the breaking window can be manipulated by changing the Fermi energy of the BDS rods without changing the background polarization conversion pass band. Different from our former work [22] that applies EIT-like effect to break the optical chirality of asymmetric transmission, this work is oriented for THz reflection polarization conversion with the breaking window being controlled at will, which opens a new route in controlling THz waves. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, many other studies introduced graphene and disturbance to adjust the asymmetric transmissions. [18][19][20] Traditionally, magneto-optical materials 21,22 and non-linear media 23,24 were used to break the Lorentz's symmetry condition and induce the effect of nonreciprocal transmissions. However, these studies usually involve a material whose size is bigger than the desired wavelength; hence, they cannot be used in the micro-nano optical system and other optical communication systems.…”
Section: Introductionmentioning
confidence: 99%